Role of Genetic Markers in Dental Caries: A Literature Review - Sharma, Disha; Bhandary, Srikala (Journal of Health and Allied Sciences NU, 2023)
Introduction This article reviews the literature on the role of genetic markers in the initiation and progression of dental caries and provides a modern understanding of the disease etiology. Dental caries is a complex, chronic, multifactorial disease which is influenced by genetic, environmental, and social factors. Identification of genetic risk factors will help screen and identify susceptible patients to better understand the contribution of genes in caries etiopathogenesis to formulate various diagnostic and novel therapeutic approaches in the management of the disease.Materials and Methods Innovations and ideas were retrieved based on the literature in journals and textbooks indexed in PubMed, Google Scholar, Scopus, and Web of Science database. The theories obtained are then summarized into a continuous series; thus, readers can more easily understand the ideas and innovations offered.Results Through interactions of the involved gene products, genetic markers have been constructed and provide us with insights into the molecular mechanisms underlying caries. There can also be gene–gene interactions or gene–environment interactions that create epigenetic effects that all possibly contribute to caries risk and resistance. A variety of caries markers have been identified, including genes affecting salivary flow rates and composition, tooth formation genes, as well as immune genes.Conclusion Information derived from various diverse studies will provide new tools to target individuals and/or populations for a more efficient and effective implementation of new preventive measures and diagnostic and novel therapeutic approaches in the management of dental caries.
Keywords: genetics; dental caries; salivary flow; extracellular matrix